2018
DOI: 10.1016/j.neurobiolaging.2018.05.017
|View full text |Cite
|
Sign up to set email alerts
|

The effect of APOE genotype on Alzheimer's disease risk is influenced by sex and docosahexaenoic acid status

Abstract: An apolipoprotein E ε4 (APOE-ε4) genotype is the strongest common genetic determinant of Alzheimer's disease (AD). The pleiotropic nature of apolipoprotein E has made elucidation of the aetiological basis difficult to establish, which is further complicated by the fact that the penetrance of the APOE-ε4 allele is modulated by sex, age, and nutrition. A greater metabolic consequence of the APOE-ε4 allele is likely to contribute to the fact that two-thirds of AD patients are female. A higher tissue status of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 154 publications
(124 reference statements)
2
33
1
Order By: Relevance
“…Our results are in line with observations reported in the Global Alzheimer's Association Interactive Network meta-analysis that showed the influence of sex on cognitive decline emerged as age dependent (6). Women carrying 1 or 2 copies of the APOE4 allele were at a higher and earlier risk of MCI (at ages 55-70 yr) or AD (at ages 65-75 yr) compared with men, with sexual dimorphism ceasing after 75 yr (5,6) [for review (30)].…”
Section: Lower Cortical Dha Content In Old Female Apoe4 Micesupporting
confidence: 88%
See 1 more Smart Citation
“…Our results are in line with observations reported in the Global Alzheimer's Association Interactive Network meta-analysis that showed the influence of sex on cognitive decline emerged as age dependent (6). Women carrying 1 or 2 copies of the APOE4 allele were at a higher and earlier risk of MCI (at ages 55-70 yr) or AD (at ages 65-75 yr) compared with men, with sexual dimorphism ceasing after 75 yr (5,6) [for review (30)].…”
Section: Lower Cortical Dha Content In Old Female Apoe4 Micesupporting
confidence: 88%
“…Here, we observed a lower percentage and concentration of cortex DHA in older female APOE4 mice compared with their APOE3 or male counterparts. Previous studies in rodents have demonstrated the impact of aging on brain DHA (29) and identified DHA transporters across the blood-brain barrier using transgenic animal models [for review (30)]. Vandal et al (31) described the impact of APOE4 genotype on DHA uptake.…”
Section: Lower Cortical Dha Content In Old Female Apoe4 Micementioning
confidence: 99%
“…Apolipoprotein E (APOE) genotype is the strongest prevalent risk factor for neuropathology and AD (Liu et al, 2013;Neu et al, 2017;Pontifex et al, 2018). ApoE was originally identified as a component of systemic circulating lipoproteins and a member of a family of apolipoprotein modulators of their metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, 50-70% of populations present with the APOE3/E3 genotype, with the ε3 allele accounting for 70-80% of the gene pool, and the ε2 and ε4 allele accounting for 5-10% and 10-15% respectively (Huang et al, 2004). APOE4 carrier status is highly predictive of dementia and AD, with APOE3/E4 and APOE4/E4 being at 3-4 and 8-12 fold increased risk and a much earlier age of onset (Pontifex et al, 2018). Although the aetiological basis of APOE4-neuropathological associations has been widely researched and reported, the main aetiological mechanism has not been clearly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Almost two thirds of cases of dementia are in women. The cause of this difference between the sexes is poorly understood 2…”
mentioning
confidence: 99%